The Effectiveness of Social Media in Preventing the Crime of Theft with Aggravating Circumstances by Bhabinkamtibmas Binmas Unit of Singosari Police Malang Police - Bhayangkara, Diva Ananta (Advances in Police Science Research Journal, 2024)
Cases of weighted theft in the Malang area have increased significantly during the last three years. Malang Police need to take preventive action by involving Bhabinkamtibmas to increase public awareness. Bhabinkamtibmas is expected using social media to provide appeals so that the public is more alert to cases theft. The goal is to increase community participation and maintain security in village or sub-district environment. Further research can be carried out with a qualitative approach to understand more deeply this phenomenon. However, Bhabinkamtibmas Singosari Police faced this challenges in preventing theft are serious due to limited personnel and multiple tasks. The use of social media for prevention is less effective because the content is less focused on local security and more about viral issues.